The Oral Status Survey Tool: construction, validity, reliability and feasibility among people with mild and moderate intellectual disabilities. Issue 5 (15th March 2021) - Mac Giolla Phadraig, C.; Ishak, N. S.; van Harten, M.; Al Mutairi, W.; Duane, B.; Donnelly‐Swift, E.; Nunn, J.
Abstract: Background: A lack of robust data about the oral health of people with intellectual disabilities (IDs) contributes to health disparities. Appropriate research tools are therefore needed. This study reports the construction and evaluation of the Oral Status Survey Tool (OSST), designed to be administered with people with disabilities by non‐dental personnel. Method: Oral Status Survey Tool construction and evaluation was achieved adopting a non‐clinical construction and content validation phase and a clinical phase to test concurrent validity, reliability and feasibility . Final refinements were also made. Results: The OSST conceptual framework covered oral function ( tooth count, denture wear and opposing pairs of teeth ) and oral disease/treatment need ( soft tissue status, oral cleanliness, gum condition, carious teeth and oral pain ). A systematic literature review identified no existing suitable indices. Candidate items were identified and validated by experts generating content validation ratios. This framework was modified later to expand the function construct. In the initial clinical phase, 49 out of 60 participants underwent examination with OSST and standard dental assessments. All had mild to moderate IDs. Mean age was 43 years (SD = 16), and mean number of teeth was 22.1 (SD = 8.6). Data collectors included two dentists and three non‐dentists. Later, a further 17 adults (nine female and eight male) with mild/moderate IDs were included for refinement. At this stage, data collectors included two dentists and five non‐dentists. Concurrent validity was established for tooth count [intraclass correlation coefficient = 0.99 (95% confidence interval, CI: 0.99–0.99)], carious teeth [Gwet's AC2 = 0.94 (95% CI: 0.89–0.99)] and gum condition [Gwet's AC1 = 0.84 (95% CI: 0.64–1)]. For all final OSST items, inter‐rater reliability ranged from moderate to very good; median test–retest reliability ranged from moderate to good. Acceptability was demonstrated for data collectors and participants. Mean time to complete the OSST was 7 min. Conclusions: The OSST is a novel tool that can record a range of clinical oral features including tooth count, denture wear, occluding pairs of teeth and functional dentition, oral cleanliness, gum condition, carious cavitation and oral pain that will be useful within health surveys of people with mild–moderate IDs and similarly neglected populations. The tool demonstrates promising attributes and acceptability. From this study, the OSST appears to be a robust tool that can be incorporated into general data collection for people with mild–moderate IDs and similar populations. A key feature is that it can be administered by well‐trained non‐dentists.